2022
DOI: 10.3389/falgy.2022.875295
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Airway Remodeling and Inflammation: Clinical and Biological Factors

Abstract: Asthma is characterized by an increase in the contraction and inflammation of airway muscles, resulting in airflow obstruction. The prevalence of asthma is lower in females than in males until the start of puberty, and higher in adult women than men. This sex disparity and switch at the onset of puberty has been an object of debate among many researchers. Hence, in this review, we have summarized these observations to pinpoint areas needing more research work and to provide better sex-specific diagnosis and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 210 publications
0
6
0
Order By: Relevance
“…26 Moreover, gender differences in sex hormone levels and respiratory control during development exist, which further contribute to the greater susceptibility of boys to respiratory diseases compared to girls. 27,28 Our study found no significant effect of PM 10 on AURI hospitalization in children across all age groups in the age-stratified analysis. However, PM 2.5 exhibited a significant effect on AURI hospitalization in children of all age groups, with the highest impact observed in children aged 0-1 years.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…26 Moreover, gender differences in sex hormone levels and respiratory control during development exist, which further contribute to the greater susceptibility of boys to respiratory diseases compared to girls. 27,28 Our study found no significant effect of PM 10 on AURI hospitalization in children across all age groups in the age-stratified analysis. However, PM 2.5 exhibited a significant effect on AURI hospitalization in children of all age groups, with the highest impact observed in children aged 0-1 years.…”
Section: Discussionmentioning
confidence: 49%
“…Boys tend to spend more time in outdoor activities compared to girls, which increases their susceptibility to exposure and subsequent impacts of air pollutants 26 . Moreover, gender differences in sex hormone levels and respiratory control during development exist, which further contribute to the greater susceptibility of boys to respiratory diseases compared to girls 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we only used female mice for all the indicated experiments. This difference may be mainly due to the differences in sex hormones and innate immune types, which result in a stronger Th2-type inflammation in females, rather than different types of immune responses (44). In our study, female mice, which are known to be more prone to developing allergic airway inflammation, were chosen as the subjects for this research.…”
Section: Discussionmentioning
confidence: 99%
“…Female Balb-c mice (8–10 weeks old) were randomly assigned into three study groups: (1) Control, (2) OVA + vehicle, and (3) OVA + BIBF1000. The reason for choosing female mice is based on the previous studies that female mice experience more airway remodeling compared with male mice [ 21 ], and that adult women are more susceptible to developing asthma than men and that women display more severe forms of the disease [ 22 ]. The study protocol is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%